A Study on Socio-Demographic Determinants of Digital Financial Literacy in India - PATTNAYAK, Nirmala Chandra; SAHOO, Rashmita (Theoretical and Practical Research in Economic Fields, 2024)
Digital financial literacy has emerged as a key driver for fostering financial inclusion in India. As India has been witnessing rapid digitalization of financial services, digital financial literacy has become an imperative because of it’s transformative potential to spread awareness, knowledge and influence user behaviors towards adoption of digital financial services. The purpose of this study was to investigate relationships between various socio-economic and demographic factors and digital financial literacy variables in both rural and urban areas of India. The study relied on a mix of quantitative surveys and qualitative interviews from the respondents belonging to urban and rural areas spread across eight districts of India. The primary data collected underwent several statistical analyses, including the Chi-Square Test, Cramer’s V, correlation analysis, and multiple regression analysis to examine the relationships between socio-demographic factors and digital financial literacy. The study revealed a strong positive correlation between education, age and income with digital financial literacy, underscoring their substantial impact. In contrast, other socio-demographic factors like occupation and social stratification were found to have lesser influence on the digital financial literacy in view of their weaker correlations. The study revealed that digital financial literacy is gender neutral considering negligible correlation between gender and variables of digital financial literacy. The existence of digital divide between urban and rural areas was evident in the study as the rural population lags in digital financial literacy to their urban counterparts. Regression analysis further validates the predictive significance of age, education, and annual family income on digital financial literacy. The earlier research studies and available literature emphasize mainly supply side factors of digital financial literacy viz. measures taken by Governments, Regulators and Financial institutions. This study, focusing on demand side factors, put special emphasis on social and demographic variables and their degree of influence on digital financial literacy. Key findings emerged from the study identify the socio-demographic factors influencing digital financial literacy and offer insights for policy makers to identify gaps in financial education and design targeted strategies based on socio-demographic parameters for broadening digital financial literacy.